PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY OF CATHARANTHUS ROSEUS L.(G.) DON - K. Rekha, Prof. M. Mamatha, (Chelonian Research Foundation, 2023)
Plants serve as crucial reservoirs of pharmaceutical drugs, as well as being utilized in traditional medicine for therapeutic intentions. While it is possible to create these substances in a laboratory setting, the process of synthesizing them is challenging, leading to limited production and impractical economic feasibility. Catharanthus roseus L.(G.) Don. is a deciduous perennial plant with dark green and lustrous foliage that belongs to the Apocyanaceae family which is rich in alkaloids and medicinal properties. The phytochemical screening of Catharanthus roseus leaves showed that the presence of Saponins, Tannins, Triterpenes, Alkaloids, Flavonoids and starch. In antibacterial activity, leaf extract showed high activity against Bacillus subtilis and Streptococcus pneumoniae at low concentration (25%) compared with Pseudomonas aeruginosa and Proteus vulgaris. In antifungal activity, leaf extract showed high activity against Aspergillus flavus at low concentration (25%) compared with Aspergillus niger, Rhizoctonia solani, Fusarium oxysporum. The current study generally found that Catharanthus roseus has the potential to be used for extracting plant compounds. These compounds could be used to develop scientific evidence-based antibacterial and antifungal products for treating bacterial and fungal infections in the future. Keywords: Catharanthus roseus, Phyto-chemical analysis, Antibacterial activity, Antifungal activity